Analisis Dampak Penerapan Kebijakan PSAP 17 Properti Investasi Pada BPKAD Kabupaten Bangkalan - Ageng Triganda; Hilda Septia S; Nabilla Rivanti; Mas Ayu Desvinta N; Nura Afifah; Mohamad Djasuli (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
The Regional Financial and Asset Management Agency (BPKAD) is an agency that carries out government affairs as a guideline for managing local regional finances and property, implementing technical support, monitoring, evaluation, and technical guidance when carrying out affairs support functions, implementing agency administration and executor of other functions assigned by the regent according to the field. This research aims to evaluate the impact of implementing PSAP 17 Investment Property on Regional Property in the form of managed assets and obstacles in implementing an accounting system that is by applicable regulations. The method used in this research is qualitative research with a literature study approach and case studies on assets managed by BPKAD Bangkalan Regency. The research results show that the implementation of PSAP 17 Investment Property has an impact on financial reporting at BPKAD, with the obstacle being that there is no account code related to investment property. This research provides a solution to this problem by developing a recording system for assets that is implemented and managed by the agency in accordance with applicable regulations.